Predictive Value of Carotid-femoral Pulse Wave Velocity for Major Adverse Cardiovascular Events and All-cause Mortality in Different Age Groups of a Chinese Community - Jin Zheng; Xiaona Wang; Li Mao; Ping Ye (Cardiology Discovery)
Objective:. To investigate the predictive value of carotid-femoral pulse wave velocity (cf-PWV) for assessing major adverse cardiovascular events (MACE) and all-cause mortality in different age groups of a Chinese community. Methods:. This is an observational study which enrolled 1,325 individuals from a community in Beijing from September 2007 to October 2018. They were classified based on age into <65-year-old (n = 572) and ≥65-year-old (n = 753) groups, and on cf-PWV into cf-PWV <12 m/s (n = 501) and cf-PWV≥12 m/s (n = 824) group. The incidence rates of MACE and all-cause mortality were recorded for both the groups during the follow-up period of 9.5 years. The predictive value of cf-PWV for MACE and all-cause mortality in the 2 age groups was estimated using the Cox proportional hazards regression models. Results:. The baseline cf-PWV showed positive correlation with age (r = 0.462, P < 0.001). During the follow-up period, 191 MACE and 84 all-cause mortality cases were recorded in the study population. The incidence rates of MACE (χ2 = 27.196, P < 0.001) and all-cause mortality (χ2 = 9.473, P = 0.002) were significantly higher in subjects with cf-PWV ≥12 m/s than in subjects with cf-PWV <12 m/s. Cox proportional hazards regression model analyses demonstrated that cf-PWV was an independent risk factor in the <65-year-old group for MACE (hazard ratio: 1.310; 95% confidence interval: 1.007–1.560; P = 0.038) and all-cause mortality (hazard ratio: 1.412; 95% confidence interval: 1.133–1.936; P = 0.005) after adjusting for several risk factors. However, both univariate and multivariate analyses demonstrated that cf-PWV was not an independent risk factor for MACE or all-cause mortality in the ≥65-year-old group (P > 0.05). Conclusion:. cf-PWV, a measure of arterial stiffness, emerged as an independent risk factor for MACE and all-cause mortality in subjects below 65 years of age.